TRIGONOMETRIC FUNCTIONS IN TAXICAB GEOMETRY FORMULAS FOR SINE AND COSINE OF SUM AND DIFFERENCE OF TWO ANGLES, FORMULAS FOR SUM AND DIFFERENCE OF SINE AND COSINE FUNCTION - Kausar, Al
Taxicab geometry is one of many non-Euclidean geometries in which the distance between the two points and is not the length of line segment AB as in Euclidean geometry, but the sum of the absolute values of differences between coordinates A and B, which is . In this project, consequences of using the taxicab concept of distance in the understanding of angles, trigonometric relations, and trigonometric functions, especially the functions of sine and cosine are studied. Futhermore, using the new notions of angle and trigonometric functions, we obtain the formulas of sine and cosine taxicab functions of the sum and differences of two angles. We also obtain formulas of the sum and differences of sine and cosine taxicab functions.